Probabilidade e estatística aplicadas ao esporte - Ribeiro, Rafael do Nascimento Tomé (Universidade Federal Rural do Semi-Árido, 2016)
The present work has as main purpose to study the importance of applying probability and statistics in sports, especially in football. It can be used to satisfy the curiosity of those interested in the sport, how the probability and statistics are calculated and used for the development of this sport ,based on a bibliographic research showing the basic concepts, definitions, presentation of a model for the calculation of probabilities in football, statistics data can be collected and showed how they are obtained. Indeed, this research may contribute to the further study of teachers, students and others interested in the subject
Keywords: Probabilidade; Estatística; Esporte; Futebol; Probability; Statistics; Sport; Football; CIENCIAS EXATAS E DA TERRA::MATEMATICA